Experiences of university faculty members regarding communication in work environment - Mehrabi, Tayebeh (Medknow Publications Pvt Ltd, 2010)
BACKGROUND: Individuals have different understandings, beliefs, values and attitudes, and follow their own specific approach to express their feelings. The present research was aimed to study the experiences of the faculty members of nursing and midwifery department regarding communication in work environment. METHODS: As the phenomenon to be studied in the current research is the human experiences, the study was accomplished in nursing and midwifery department of seven universities, including Isfahan, Shahid Beheshti, Tehran, Iran, Mashhad, Shiraz, and Tabriz universities of medical sciences. The most common data collection technique in qualitative studies is the participants’ observations, interview, and their written texts. In the present study, Collaizzi's seven steps were applied. RESULTS: We interviewed 36 individuals, including 20 women and 16 men. The intra-organizational communications influence the physical and mental health as well as performance of staffs in their work environment. CONCLUSIONS: This study expressed in the themes formulated from statements of the units under study.